2006
DOI: 10.1128/aem.00506-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gene Cluster for Biosynthesis of Mannosylerythritol Lipids in the Basidiomycetous Fungus Ustilago maydis

Abstract: Many microorganisms produce surface-active substances that enhance the availability of water-insoluble substrates. Although many of these biosurfactants have interesting potential applications, very little is known about their biosynthesis. The basidiomycetous fungus Ustilago maydis secretes large amounts of mannosylerythritol lipids (MELs) under conditions of nitrogen starvation. We recently described a putative glycosyltransferase, Emt1, which is essential for MEL biosynthesis and whose expression is strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(141 citation statements)
references
References 37 publications
1
139
0
1
Order By: Relevance
“…Even though we could not de- tect the metabolite MEL in the liquid culture with the sampling techniques we used, we did find expression of genes involved in MEL biosynthesis (10). As seen with ustilagic acid, expression of the genes involved in MEL biosynthesis is detected in single cultures after 2 days but almost completely absent in cocultivation cultures (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Even though we could not de- tect the metabolite MEL in the liquid culture with the sampling techniques we used, we did find expression of genes involved in MEL biosynthesis (10). As seen with ustilagic acid, expression of the genes involved in MEL biosynthesis is detected in single cultures after 2 days but almost completely absent in cocultivation cultures (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The longest lipid moiety of ustilagic acid has been reported to hydroxilated C16:0 but for mannosylerytritol lipids C 14 , C 16 and C 18 saturated and unsaturated fatty acids were found although sucrose was the carbon source [8] [33]. The enzymes involved in the biosynthesis of the glycolipids (UA and MEL) have been described in [11] [12]. For UA a cytochrome P450 monooxygenase Cyp1 catalyzes terminal hydroxylation of palmitic acid and cyp2 is required for subterminal hydroxylation (w-1 hydroxylation) of this fatty acid [1] [12].…”
Section: Discussionmentioning
confidence: 99%
“…For UA, cyp1 and cyp2 genes are required for terminal and subterminal hydroxylation of hexadecanoic acid [12]. Mannosylerythritol lipids (MEL) are secreted in at least four different varieties (ABCD), depending on the number of acetyl groups attached to the disaccharide [3]- [11] and a glycosyltransferase is essential for the biosynthesis of MEL; expression of this enzyme is strongly induced by limitations on nitrogen availability [11]. To produce these glycolipids, U. maydis requires raw materials to synthesize the lipid and carbohydrate moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the identified ESTs encoded putative proteins that are directly involved in the sensing of stress and in the defence response (Iakovlev and Stenlid, 2000;Kültz, 2005;Horan et al, 2006;Gucciardo et al, 2007). Proteins known to be involved in the nutrient starvation response (Schmelzle et al, 2004;Aro et al, 2005, Hewald et al, 2006 were also identified, which is comparable to that found in P. anserina (Federovo et al, 2005;Pinan-Lucarré et al, 2003, 2007. qRT-PCR analyses on A. areolatum made it possible to further show that transcripts encoding putative defence response proteins were strongly up-regulated only in the vegetatively incompatibile interactions, while the results of the laccase staining experiments showed that laccases most likely contribute to the protection of cells (Eisenman et al, 2007) during vegetatively incompatibility.…”
Section: Discussionmentioning
confidence: 99%